Nudging Eyeglass Use Among Children: Evidence from a Randomized Controlled Trial in Vietnam - Cuong Viet Nguyen; Quynh Thien Thi Pham; Tung Duc Phung (Global Labor Organization (GLO), 2025)
In this study, we examine whether a nudging intervention increases eyeglass use among primary and lower-secondary students in Vietnam through a randomized controlled trial. Students with refractive errors in 34 schools in one province were provided with free eyeglasses. Half of the schools were randomly selected, allowing students in these schools to choose from 10 available eyeglass frames. Six months after receiving their eyeglasses, we assessed the impact of frame choice. We find no significant effect of frame choice on students' eyeglass-wearing behavior.
Keywords: I12; I20; C93; 330; Education; Health; Randomized Control Trial; Nudge; Vietnam